Field evaluation of furrow and drip irrigated potatoes for water and energy productivities : a case study in Kasur District of Punjab, Pakistan - Asif, Muhammad; Babel, Mukand Singh; Shanmugam, Mohana Sundaram; Shrestha, Sangam; Datta, Avishek; World Bank; Punjab Agriculture Department, Pakistan (Pathum Thani, Thailand : Asian Institute of Technology, 2020)
Eight farmers{u2019} fields of different energy sources of the furrow and drip-irrigated potatoes were selected to evaluate water and energy productivities as a case study in the Kasur district of Punjab, Pakistan. Quantification of water and energy, examining the potato growth and yield, parameters assessing CO2, and finding water, energy. and yield indicators were carried out for potatoes in farmers{u2019} fields of Kasur district of Punjab. Pakistan. Discharge is measured by the trajectory method in the furrow irrigation method, but flow meter is used in the case of a drip irrigation method. An electric meter is being used for both drip and furrow method for energy measurements. yield is measured by a random selection of three beds of one square meter area from start middle and end of the field and converted into one hectare The study revealed that 42% water could be saved with 25% more energy consumption in drip irrigation method and electric energy source as compared to furrow irrigation method Potato production of drip-irrigated potatoes is as high as 28.2 ton/ha of the electric energy source as compared to 17.1 ton/ha lowest production of furrow irrigated potatoes of diesel energy source Drip irrigated potatoes germinate three to four days earlier as compared to furrow irrigated potatoes, There is not any significant impact of plant height and no. of tubers/plant for both drip and furrow irrigated potatoes with different energy sources Water productivity has no relationship with energy sources. Water productivity of drip-irrigated potatoes is almost three times more as compared to furrow irrigated potatoes. Water and water-energy productivities of drip-irrigated potatoes are as high as 15 kg/MJ and 0.0053 {(kg/(m3*MJ)}.for electric energy source and as low as 3.06 kg/MJ and 0.0007 {(kg/(m3*MJ)}.for diesel energy source respectively.CO2 emission (kg/kg) potato production is as low as 0.0107 and 0.0113 (kg/kg) in solar and electric energy source respectively and as high as 0.0237 (kg/kg) in diesel energy source Overall response of yield, water, and energy productivities and CO2 emission of drip-irrigated potatoes is more as compared to furrow irrigated potatoes to save water, energy and keep the environment safe
Thesis (M. Eng.) - Asian Institute of Technology, 2020
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Keywords: Microirrigation -- Pakistan -- Punjab; Crops and water -- Pakistan -- Punjab; potatoes -- Pakistan -- Punjab